The Oxford Handbook of Ancient Nubia 2021
DOI: 10.1093/oxfordhb/9780190496272.013.9
|View full text |Cite
|
Sign up to set email alerts
|

The Pre-Kerma Culture and the Beginning of the Kerma Kingdom

Abstract: The Pre-Kerma is an Upper Nubian culture that developed between 3500 and 2500 bce. It preceded the Kerma civilization and was in part contemporaneous with the A-Group from Lower Nubia. It consisted of an agro-pastoral population that maintained contacts with Lower Nubia and produced pottery somewhat similar to that of the A-Group. It is best known from settlements dated between 3000 and 2600 bce, in particular those from Kerma and Sai Island. The settlement sites have yielded a large number of cereal storage p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Situated within a regional context, the results of this study suggest a later economic transition in Upper Nubia postdating the suggested Late Neolithic hiatus on the alluvial plain (Fig 16 and Table 3) [25,27,45]. Although recently published dates from KDK5A and KDK5B indicate some occupation continuity during the early 4 th millennium BCE [75], there is clearly a significant reduction in the number of sites on the alluvial plain at the end of the 5 th millennium BCE [27,241,242]. The limited archaeological evidence for Late Neolithic groups on the alluvial plain during the early-to mid 4 th millennium BCE correlates with the progressive drying up of the desert wadis combined with an episode of reduced Nile flow and floodplain contraction [27,29,163].…”
Section: Plos Onementioning
confidence: 73%
“…Situated within a regional context, the results of this study suggest a later economic transition in Upper Nubia postdating the suggested Late Neolithic hiatus on the alluvial plain (Fig 16 and Table 3) [25,27,45]. Although recently published dates from KDK5A and KDK5B indicate some occupation continuity during the early 4 th millennium BCE [75], there is clearly a significant reduction in the number of sites on the alluvial plain at the end of the 5 th millennium BCE [27,241,242]. The limited archaeological evidence for Late Neolithic groups on the alluvial plain during the early-to mid 4 th millennium BCE correlates with the progressive drying up of the desert wadis combined with an episode of reduced Nile flow and floodplain contraction [27,29,163].…”
Section: Plos Onementioning
confidence: 73%
“…A hundred and fourteen remains from the 17 Holocene archaeological sites were sampled (electronic supplementary material, table S2). Seventeen specimens come from the sites of Muweis and Kerma in Sudan [60]; 48 from Wakarida [61], Mota Cave [62], Kumali [63], Garu [64], Kurub 7 and the Kurub Bahari plain [65], Asa Koma [66], Wakrita [67], Hedaito le Dora, Laas Geel [68], respectively, in Ethiopia, Djibouti and Somaliland; 11 from Prolonged Drift [69] and Vaave Makonge [70] in Kenya for eastern Africa. Southern African sites included fifty-three specimens from Geduld [71] and Leopard Cave [72] in Namibia; Toteng 1 and 3 [73] in Botswana and Melikane in Lesotho [74].…”
Section: Archaeological Faunal Remainsmentioning
confidence: 99%
“…Understanding the scale, time depth, and cultural ramifications of mobile pastoralists' interactions with semi‐sedentary Nilotic foraging groups in Middle Nile Valley is critical because the meeting of these two economies is associated with drastic social and political changes that underlay the social complexity seen in the ancient African kingdom of Bronze Age Kerma (Chaix et al, 2015; Honegger, 2019, 2021; Honegger & Williams, 2015; Wengrow et al, 2014). The interaction and the struggle for power between herders and foragers preceding the Egyptian Predynastic era has been well‐studied (Hassan, 1988; Hendricks, 2013; Wengrow, 2006; Wengrow et al, 2014); however, details of this same phase in Sudan are much less well known.…”
Section: Introductionmentioning
confidence: 99%